2008
DOI: 10.1186/1476-4598-7-88
|View full text |Cite
|
Sign up to set email alerts
|

Membrane androgen receptor activation triggers down-regulation of PI-3K/Akt/NF-kappaB activity and induces apoptotic responses via Bad, FasL and caspase-3 in DU145 prostate cancer cells

Abstract: Background: Recently we have reported membrane androgen receptors-induced apoptotic regression of prostate cancer cells regulated by Rho/ROCK/actin signaling. In the present study we explored the specificity of these receptors and we analyzed downstream effectors controlling survival and apoptosis in hormone refractory DU145-prostate cancer cells stimulated with membrane androgen receptor-selective agonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 45 publications
(68 reference statements)
3
49
0
Order By: Relevance
“…In the presence or absence of 10 26 mol l 21 wortmannin (Sigma), they were stimulated in serum containing medium with 10 27 mol l 21 of testosterone-HSA for 12 h. Untreated cells cultured in serum free medium were used as positive control for the apoptotic response.After the indicated time periods, medium was discarded, and apoptosis was assayed using the APOPercentage Apoptosis Assay kit (Biocolor Ltd), as previously described. 9 The assay uses a dye which is imported by cells undergoing apoptosis, when the 'flip-flop' mechanism translocate phosphatidylserine to the outer membrane leaflet. The dye has a purple-red color.…”
Section: Rac1 Activation Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…In the presence or absence of 10 26 mol l 21 wortmannin (Sigma), they were stimulated in serum containing medium with 10 27 mol l 21 of testosterone-HSA for 12 h. Untreated cells cultured in serum free medium were used as positive control for the apoptotic response.After the indicated time periods, medium was discarded, and apoptosis was assayed using the APOPercentage Apoptosis Assay kit (Biocolor Ltd), as previously described. 9 The assay uses a dye which is imported by cells undergoing apoptosis, when the 'flip-flop' mechanism translocate phosphatidylserine to the outer membrane leaflet. The dye has a purple-red color.…”
Section: Rac1 Activation Assaymentioning
confidence: 99%
“…[2][3][4][5][6][7] Activation of these binding sites by no permeable testosterone albumin conjugates (TACs), was shown to induce strong proapoptotic and anti-tumorigenic effects on various tumors both in vitro and in vivo. 2,6,8,9 The molecular mechanisms governing these effects have been elucidated and specific signaling cascades triggered by the stimulation of membrane androgen receptors (mARs) have been described in prostate and breast tumor cells. 4,5,[9][10][11] Functional membrane androgen binding sites have been also reported in colon cancer cells and tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, long term down regulation of the pro-survival PI-3K/Akt pathway became evident 12-24 h upon mAR activation as indicated by the significant decrease of the phosphorylation levels of PI-3K and Akt. Furthermore, inhibition of NF-jB translocation and increased FasL expression were documented, while increased caspase 3 activity was measured (38). These events were regulated by mAR-induced Rho/ ROCK/actin signaling, as indicated either by transfection experiments with dominant negative mutants or by pharmacological inhibitors of this pathway.…”
Section: Membrane Androgen Receptor Signaling In Human Cancer Cells Mmentioning
confidence: 99%
“…The mAR-dependent nongenomic signaling was recently characterized in detail in prostate and breast cancer cells (15), and key prosurvival and proapoptotic gene products were identified that regulate the apoptotic response induced by mAR activation (16). According to these reports it was postulated that mAR might be a significant novel target for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%